Factors associated with disordered eating and eating disorder symptoms in adolescent elite athletes - Nadja Walter; Thomas Heinen; Anne-Marie Elbe (Hogrefe AG, 2022)
Abstract. Introduction: Recent studies indicate high prevalences of disordered eating or eating disorders in adult athletes and a worrying increase in adolescent athletes. Although several risk factors for developing eating disorders have been identified for adult athletes (e.g., personality factors, sport-related pressure), research on risk factors in adolescent athletes is scarce. Methods: This study investigates the prevalence of disordered eating and eating disorder symptoms and its association with personality- and sport-related risk factors in a sample of 439 elite athletes aged 13-18 years. Self-regulatory personality factors, sports and social pressure, as well as sports biographical data, were investigated in relation to different weight control methods and the Eating Disorder Examination Questionnaire measuring disordered eating and eating disorder symptoms. Results: Results indicate a prevalence rate of clinically significant eating pathology of 5.5% for the total sample, in which female athletes aged 15-18 years show the highest rate (9.6%). The structural equation model indicates a predominant association of sports and social pressure and personality factors with eating disorder symptoms. Conclusion: Being in the age range 15-18 years, being female, and being an athlete in a high-risk sport (e.g., aesthetics, weight class, or endurance sports) were identified as risk factors as well as athletes' mental association with weight loss and success, and athletes' perceived social pressure on eating and on body shape. Disordered eating and eating disorders are not only of concern for adults but also for young elite athletes and recommendations for adolescent elite athletes, coaches, and parents are given.